The Transcription Factor AP-2β Causes Cell Enlargement and Insulin Resistance in 3T3-L1 Adipocytes - Tao, Yukari; Maegawa, Hiroshi; Ugi, Satoshi; Ikeda, Kazuhiro; Nagai, Yoshio; Egawa, Katsuya; Nakamura, Takaaki; Tsukada, Shuichi; Nishio, Yoshihiko; Maeda, Shiro; Kashiwagi, Atsunori (Endocrinology (Philadelphia), 2006)
We have reported the association of variations in the activating protein-2β (AP-2β) transcription factor gene with type 2 diabetes. This gene was preferentially expressed in 3T3-L1 adipocytes in a differentiation stage-dependent manner, and preliminary experiments showed that subjects with the disease-susceptible allele showed stronger expression in adipose tissue than those without the susceptible allele. Thus, we overexpressed the AP-2β gene in 3T3-L1 adipocytes to clarify whether AP-2β might play a crucial role in the pathogenesis of type 2 diabetes through dysregulation of adipocyte function. In cells overexpressing AP-2β, cells increased in size by accumulation of triglycerides accompanied by enhanced glucose uptake. On the contrary, suppression of AP-2β expression by small interfering RNA inhibited glucose uptake. Enhancement of glucose uptake by AP-2β overexpression was attenuated by inhibitors of phospholipase C (PLC) and atypical protein kinase Cζ/λ (PKCζ/λ), but not by a phosphatidylinositol 3-kinase (PI3-K) inhibitor. Consistently, we found activation of PLC and atypical PKC, but not PI3-K, by AP-2β expression. Furthermore, overexpression of PLCγ enhanced glucose uptake, and this activation was inhibited by an atypical PKC inhibitor, suggesting that the enhanced glucose uptake may be mediated through PLC and atypical PKCζ/λ, but not PI3-K. Moreover, we observed the increased tyrosine phosphorylation of Grb2-associated binder-1 (Gab1) and its association with PLCγ, indicating that Gab1 may be involved in AP-2β-induced PLCγ activation. Finally, AP-2β overexpression was found to relate to the impaired insulin signaling. We propose that AP-2β is a candidate gene for producing adipocyte hypertrophy and may relate to the abnormal characteristics of adipocytes observed in obesity.